The force, velocity, and power of the lower limbs as determinants of speed climbing efficiency - Krawczyk, Marcin; Pociecha, Mariusz; Ozimek, Mariusz; Draga, Paweł (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Speed climbing is different from the other climbing specializations because high efficiency in this competition is primarily determined by the high efficiency of lower limbs. The assessment of the magnitude of the relations between the level of force, velocity, and power of a single jump with the level of the specific-climbing power and time of a climbing runmay have a high informative value. Material and Methods. Participants in the research were men (n = 8), taking part in the Czech Republic’s Open formula speed climbing championships. Motor performance was measured using the countermovement jump (CMJ). The measurements were made with the use of My Jump application. The analyses assessed power, force, and velocity during a CMJ jump. The Margaria–Kalamen formula was used to estimate the special climbing power. Results. The data indicate that velocity, power, the height of the CMJ jump, and the special climbing power closely correlate with climbing time. Statistically significant correlations were noted between the special climbing power and velocity, power, and height of the CMJ. Conclusions. In speed climbing running time and climbing power is probably more strongly correlated with velocity, than the force component. My Jump app can become a worthy diagnostic tool, being able to provide information about kinetic parameters, which is highly valuable for speed climbing coaches.
Keywords: explosive capacities; lower limbs; Samozino et al. method; mechanical characteristics